Cassava roots meal in diets for broilers - Brum, Paulo Antônio R. de; Guidoni, Antônio Lourenço; Albino, Luiz Fernando T.; César, José Samuel (Pesquisa Agropecuaria Brasileira, 2014)
Two experiments were conducted in two seasons, to test the influence of com (Zea mays L.) substitution by cassava roots meal (CRM) in lhe diets on the performance of broilers. In both experiments lhe leveis of substitution were O, 33.33, 66.66% and a diet without corn. In each experiment, 736 day-old broilers were allocated into floor pens which had capacity of 46 broilers per pen (23 female and 23 male). The data were analyzed according to a randomized block design with four treatments and four replications. Feed and water were supplied ad libitum. Averages feed intake, weight gain and feed conversion ratio were analyzed in the following periods: 1 to 28; 1 to 42 and 1 to 56 days of age. It was concluded that it is possible to substitute corn by CRM up to 66.66% for lhe broilers diet during the first 42 days of age. Birds reared untill 56 days can be fed diets based on CRM and soybean meal. To use these levels of CRM in the diets the other nutrient requirements must be met.